Pendapat Syaikh Nizhamuddin Al-Balkhi dalam Kitab Fatawa Al-Hindiyyah tentang Ittishal antara Ijab dan Kabul Akad Nikah - Asep Koswara; Hasan Bisri; Ayi Ishak Sholih Muchtar (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2019)
Marriage is considered valid if it has fulfilled the terms and conditions of marriage. Among the pillars of marriage are the consent and kabul. Based on the law of origin, the ulama agreed that the consent came from the bride, while the Kabul came from the groom. However, in the matter of ittishal between the consent and the marriage contract, the scholars have different opinions. If there is no ittishal between the consent and the marriage ceremony, then the contract is still considered valid while it is still focused on the contract procession and not for a long time. The objectives of the research are, (1) knowing and analyzing the opinion of Shaykh Nizhamuddin Al-Balkhi about ittishal between consent and kabul in the marriage contract, (2) knowing the basis of the legal arguments used by Shaykh Nizhamuddin Al-Balkhi regarding ittishal between consent and kabul in the marriage contract, and (3) knowing the ijtihad method used in his istimbath al-hukminya. In this thesis research the writer uses qualitative research methods, namely research methods that produce descriptive data in the form of words or written utterances from people or observed behavior. This type of research is a research library. The results showed, 1) The law of ittishal between consent and the marriage of marriage according to Shaykh Nizhamuddin Al-Balkhi in the fatawa al-hindiyyah book that ittishal between ijab and kabul nikah is only fi majlisin wahidin. The ittishal of the marriage contract that is valid in Indonesia is regulated in the Islamic Law Compilation (KHI) in article 27: consent and kabul between the guardian and the prospective groom must be clear in sequence and not intermittent. 2) The legal basis used by Shaykh Nizhamuddin Al-Balkhi in the matter of ittishal between consent and kabul akad nikah, namely the hadith of the Prophet narrated by Abu Dawud. 3) The ijtihad method used by Shaykh Nizhamuddin Al-Balkhi is qiyas. Shaykh Nizhamuddin al-Balkhi confirmed that the marriage contract was one majlis but did not work with the marriage contract that was represented and in a different place with the condition that there must still be witnesses.